Nuptial Gifts in Pomacea canaliculata (Ampullariidae, Caenogastropoda): Experimental and Field Evidence about Their Function - Burela, Silvana (2014)
Pomacea canaliculata is a South American apple snail that shows a multiple mating behavior. The copulations are frequent and long lasting, and consequently the males have to face strong sperm competition. The outer gland at the base of the penis sheath secrets drops of mucus that females eat during copulation. These mucus drops are nuptial gifts, and the occurrence of them is the only known instance of this behavior in molluscs. We investigated three possible functions of the gift-giving behavior in P. canaliculata based on three hypotheses: prowler deterrence, male mating effort and paternal investment. We also quantified the frequency of nuptial gifts in two populations of P. canaliculata and its possible role in male competition. We found no aversive reaction neither in females nor in males, but females were attracted to the mucus secretion. The consumption of artificial nuptial gifts (homogenates of the outer sheath gland) had no effect on the copulation duration nor on the total number of eggs and egg masses laid by females. In the field, the frequency of nuptial gifts was almost ten times greater in the population with the highest density of snails, indicating a much higher rate of production of nuptial gifts. The proportion of couples with both nuptial gifts and a prowler males attached was significantly higher than expected by chance in the population with the highest population density. Even though our results give no support for the three hypothesized functions for the nuptial gifts in P. canaliculata, this study revealed a possible different role in male competition: the enticement of the female to remain in copulation when the other males are trying to gain access.